Ex ante and ex post willingness to pay for hosting a large international sport event - de Boer, W. I. J.; Koning, R. H.; Mierau, J. O. (Journal of Sports Economics, 2019)
Using the contingent valuation method, we estimate residents` ex ante and ex post willingness to pay (WTP) for hosting a large international sport event: The "big start" of the 2016 Giro d`Italia, which was held in the Gelderland region of the Netherlands. The percentage of residents with a positive WTP changed from 29.7% before the event to 39.3% immediately after the event, while average WTP increased significantly from €3.58 to €4.45, leading to an increase of residents` valuation from €5.8 million to €7.1 million. Additionally, following the event in the media and attending the event play an important role in explaining residents` WTP.